2006
DOI: 10.1007/s11064-006-9118-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Nitric Oxide Production in the Rat Brain after Chronic Arsenic Exposure

Abstract: Chronic arsenic exposure is associated with nervous system damage, vascular disease, hepatic and renal damage as well as different types of cancer. Alterations of nitric oxide (NO) in the periphery have been detected after arsenic exposure, and we explored here NO production in the brain. Female Wistar rats were exposed to arsenite in drinking water (4-5 mg/kg/day) from gestation, lactation and until 4 months of age. NOS activity, NO metabolites content, reactive oxygen species production (ROS) and lipid perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…It is known that the impairment of NO production is due to lower NOS protein levels, which results from decreased expression and/or increased degradation of the proteins. Previous studies reported a decrease in Ca-dependent NOS activity measured in vivo and in vitro in arsenic-exposed rats (37 ppm drinking water) with a decrease of nNOS protein levels and an increase in ROS generation and lipid peroxidation [54,55]. Quercetin supplementation to arsenic treated rats was able to increase the NOS enzyme activity in brain.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that the impairment of NO production is due to lower NOS protein levels, which results from decreased expression and/or increased degradation of the proteins. Previous studies reported a decrease in Ca-dependent NOS activity measured in vivo and in vitro in arsenic-exposed rats (37 ppm drinking water) with a decrease of nNOS protein levels and an increase in ROS generation and lipid peroxidation [54,55]. Quercetin supplementation to arsenic treated rats was able to increase the NOS enzyme activity in brain.…”
Section: Discussionmentioning
confidence: 97%
“…NO activity in the CNS has an important role in both the physiological and pathological condition and also reported a localization of nNOS in different area of the brain, such as the corpus striatum, medulla, cortex, hippocampus, hypothalamus and the cerebellum of rodents [70][71][72]. Decreased the nitrites and nitrates in the striatum of rats associated with chronic exposure to arsenite and NO production was also decreased in vitro experiment [43]. Our study too showed decreased NO production in frontal cortex; corpus striatum and hippocampus in arsenic exposed rats may be due to the lower protein levels, which could outcome from declined expression and/or increased degradation.…”
Section: Discussionmentioning
confidence: 87%
“…Monoamine neurotransmitters (NE, DA, 5-HT) contribute a major role in learning and memory and depressive-like behaviors, therefore any disruption in the neurotransmitter system in the brain after exposed to arsenic might be contributing the abnormal functions of the brain along with impairs various normal physiological functions [34,62]. It has been reported that arsenic interferes with synaptic mechanisms of release of some neurotransmitters, and is responsible for the impairment in various neurotransmitters' systems along with neurobehavioural modifications [30,37,43]. The amino acid neurotransmitter has been investigated in immature brain after the realgar treatment in rats indicate that neurotoxicity by the realgar is linked with the disturbance the levels of amino acid neurotransmitters [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neurochemical studies demonstrated changes of catecholamine content and release in several brain nuclei (Mejia et al 1997;Rodriguez et al 1998) and decreased nitric oxide production in the basal ganglia (Zarazua et al 2006), there is not yet enough experimental evidence to attribute the observed behavioral changes to a specific action of arsenic on any particular brain region. Indeed, there is scarce information about how arsenic exposure leads to those alterations, from its entrance to the brain to its particular cellular and molecular targets.…”
Section: Introductionmentioning
confidence: 99%